1998
DOI: 10.1191/026921698666334766
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in placebo-controlled trials in palliative care: dexamethasone for the palliation of malignant bowel obstruction

Abstract: To determine the effect of dexamethasone when treating malignant bowel obstruction, 35 patients were randomized to receive intravenous dexamethasone or a placebo, crossing over to the alternate treatment arm if there had been no resolution of obstruction by day 5. This was done in two consecutive studies. Patients were stratified according to whether or not they had received specific anticancer therapy within 28 days of study. In trial 1, 15 out of 22 patients 'responded' (resolution of obstruction by day 5; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 14 publications
(11 reference statements)
0
43
0
1
Order By: Relevance
“…Small uncontrolled trials have reported benefi t from corticosteroids [41], but the most effective type, dose, dosing regimen, and route of administration have not been clarifi ed. A 2008 Cochrane review identifi ed seven retrospective and two unpublished reports containing three randomized, double-blind, controlled trials of 89 patients [42] (Laval et al, personal communication, 1998). Cochrane reviewers concluded that corticosteroids may reduce bowel obstruction in patients with GI and ovarian cancers, with low rates of adverse effects.…”
Section: Medical Managementmentioning
confidence: 99%
“…Small uncontrolled trials have reported benefi t from corticosteroids [41], but the most effective type, dose, dosing regimen, and route of administration have not been clarifi ed. A 2008 Cochrane review identifi ed seven retrospective and two unpublished reports containing three randomized, double-blind, controlled trials of 89 patients [42] (Laval et al, personal communication, 1998). Cochrane reviewers concluded that corticosteroids may reduce bowel obstruction in patients with GI and ovarian cancers, with low rates of adverse effects.…”
Section: Medical Managementmentioning
confidence: 99%
“…From the morbidity data described in Hardy (Hardy 1997a;Hardy 1997b) it was not possible to distinguish morbidity due to the drug as opposed to the underlying condition. No data were supplied comparing placebo to the treatment group.…”
Section: Morbidity Datamentioning
confidence: 99%
“…It was also the smallest study in terms of size. Hardy (Hardy 1997a;Hardy 1997b) stratified the patients into those who had recently received chemotherapy and those who had not. Laval 1998 did not do this analysis.…”
Section: Heterogeneity: Clinical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hardy et al 11 reported a randomized double blind placebo controlled trial in patients with gynecological cancer. He observed bowel obstruction resolution in 13 of 35 patients with 4 mg intravenously dexamethasone given every 6 hours (total 16 mg/ day) for 5 days.…”
Section: Studies Evaluating the Role Of Steroids In Mbomentioning
confidence: 99%